Comparison of four different hematocrit assays and the effect of albumin on their measurements - Pare, Amelie; Kippen, Laura; Wagg, Catherine; Longmore, Matt; Boysen, Soren (Frontiers in Veterinary Science, 2022)
Clinical decisions are influenced by hematocrit values. Centrifugation (reference standard), conductivity, optical and impedance methods are used interchangeably to measure hematocrit. The effects of albumin, which are known to affect conductivity methods, have not been evaluated for level of agreement (LOA) between hematocrit assays in small animals. Canine venous blood was collected from 74 clinical cases and measured by centrifugation (n=72), conductivity (n=73), impedance (n=25) and optical (n=50) methods. Bland-Altman analysis determined bias (+/- SD) and 95% LOA between methods. A Kolmogorov-Smirnov test showed conductivity data was not normally distributed. Sodium values were not statistically different between groups (p = 0.45); a sub analysis was not performed due to insufficient cases of hypernatremia and hyponatremia. There was a statistically significant difference between manual (centrifugation) hematocrit values and values obtained via conductivity (p < 0.0001), optical (p < 0.0001), and impedance (p = 0.0082) methods. The conductivity method underestimated hematocrit by 2.17 +/- 2.91% (95% LOA -3.54 to 7.88), the optical method by 3.1 +/- 3.62% (95% LOA -3.99 to 10.19), and the impedance method by 2.29 +/- 3.72% (95% LOA -5 to 9.58) when compared to manual hematocrit values. The hematocrit difference between conductivity and manual methods was statistically different for low (4%, 0 - 5%), normal (3%, -5 – 8%) and high (2%, -2 – 5%), albumin concentration, respectively (p = 0.02), with post hoc analysis demonstrating that the difference occurred between the low and high albumin groups. This study confirms that abnormal albumin values can affect the conductivity method and that hematocrit values obtained via conductivity, optical and impedance methods underestimate values obtained via centrifugation. The wide level of agreement also demonstrates that care must be taken when making clinical decisions with different hematocrit methodologies.